Erweiterung eines Abelschen Satzes - Naftalewitsch, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Нафталевич. Обобщение одной теоремы Абеля A. Naftalevičius. Vienos Abelio teoremos apibendrinimas